Sex differences in reported and objectively measured sleep in COPD - Theorell-HaglÃ¶w,Jenny; Ã“lafsdÃ³ttir,Inga Sif; BenediktsdÃ³ttir,BryndÃs; GÃslason,ThÃ³rarinn; Lindberg,Eva; Janson,Christer (International Journal of Chronic Obstructive Pulmonary Disease, 2016)
Jenny Theorell-Haglöw,1 Inga Sif Ólafsdóttir,1–3 Bryndís Benediktsdóttir,2,3 Thórarinn Gíslason,2,3 Eva Lindberg,1 Christer Janson1 1Department of Medical Sciences, Respiratory, Allergy and Sleep Research, Uppsala University, Uppsala, Sweden; 2Department of Respiratory Medicine and Sleep, Landspitali University Hospital, 3Medical Faculty, University of Iceland, Reykjavík, Iceland Background: The aim was to assess and compare reported sleep disturbances and objectively measured sleep in men and women with COPD compared with controls and also explore sex differences. Methods: A total of 96 patients with COPD and 90 age- and sex-matched controls answered a sleep questionnaire, underwent ambulatory polysomnography, a post-bronchodilatory spirometry, and blood sampling. Results: Of the patients with COPD, 51% reported sleep disturbances as compared with 31% in controls (P=0.008). Sleep disturbances were significantly more prevalent in males with COPD compared with controls, whereas there was no significant difference in females. The use of hypnotics was more common among patients with COPD compared with controls, both in men (15% vs 0%, P=0.009) and women (36% vs 16%, P=0.03). The men with COPD had significantly longer recorded sleep latency than the male control group (23 vs 9.3 minutes, P<0.001), while no corresponding difference was found in women. In men with COPD, those with reported sleep disturbances had lower forced vital capacity, higher C-reactive protein, myeloperoxidase, and higher prevalence of chronic bronchitis. Conclusion: The COPD was associated with impaired sleep in men while the association was less clear in women. This was also confirmed by recorded longer sleep latency in male subjects with COPD compared with controls. Keywords: chronic obstructive pulmonary disease, sleep, polysomnography, quality of sleep, sex